2020
DOI: 10.1080/1828051x.2020.1845576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary orange and grapefruit peel on growth performance, health status, meat quality and intestinal microflora of broiler chickens

Abstract: In our experiment we studied the effect of dietary orange peel (OP) and grapefruit peel (GP) on broilers health and thigh meat quality. The experiment was conducted on 126 Cobb 500 broiler chicks, assigned to three dietary treatments with 42 broilers per group. Each treatment was conducted in 3 experimental growth boxes, corresponding to 6 replicate pens per treatment and 7 broilers per pen. The growth boxes had identical size with a capacity of 3.5 m 2 per box. Experimental dietary treatments differed from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…Other authors 41 , 42 reported that high concentration of polyphenols implies that the antioxidants of the by-products significantly increase because of its capacity to block free radicals. This relationship between polyphenols and antioxidants was also reported by others 43 , 44 . In line with our results, Karakaya et al 45 reported that different levels of antioxidants from grapeseed and their by-products were significantly (p < 0.05) effective in fresh eggs.…”
Section: Discussionsupporting
confidence: 88%
“…Other authors 41 , 42 reported that high concentration of polyphenols implies that the antioxidants of the by-products significantly increase because of its capacity to block free radicals. This relationship between polyphenols and antioxidants was also reported by others 43 , 44 . In line with our results, Karakaya et al 45 reported that different levels of antioxidants from grapeseed and their by-products were significantly (p < 0.05) effective in fresh eggs.…”
Section: Discussionsupporting
confidence: 88%
“…Natural sources such as meals, plants, fruits, essential oils, and different extracts and mixtures are important sources of carbohydrates, proteins, lipids, amino acids, and other valuable nutrients [9]. Many of them have been tested previously in other poultry trials with positive effects on health [10][11][12]. Moreover, many of these dietary supplements promote intestinal health and integrity by being rich in fibers and amino acids, which are major nutrients for maintaining intestinal mucosal integrity and supporting the growth of microorganisms in the gut [13].…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence for the benefits of using plant flavonoids in poultry production, including their positive effects on meat fatty acid composition and oxidative stability [ 1 , 32 ]. Here, we found that the citrus flavanones hesperidin and naringin beneficially modulated the fatty acid profile of broiler chicken meat and fat pads ( Table 3 , Table 4 and Table 5 ).…”
Section: Discussionmentioning
confidence: 99%